EKKLESIOLOGI GEREJA DALAM RELASI KESETARAAN DAN KEADILAN GENDER - Apriani Magdalena Sibarani (Majalah Ilmiah METHODA, 2021)
Gender injustice is a challenge in Indonesian society in general and sadly this condition is still happening in the church which should teach and proclaim love, equality and justice for women and men as the image and of God. In this regard, the author will outline the roles and challenges of women in church ministry, the elements that affect the inequalities and injustices experienced by women in church ministry. Furthermore, the author also explores the thoughts and experiences of John Wesley as a "Methodist Father" regarding the role of women in church ministry. The exploration of John Wesley's traditions and thoughts is also one of the elements that need to be considered in recommending church ecclesiology that embodies gender equality and justice relations.